2016
DOI: 10.1002/adv.21789
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of compression‐molded green composite sheets made of poly(3‐hydroxybutyrate) reinforced with long pita fibers

Abstract: Novel green composites were successfully prepared from bacterial poly(3hydroxybutyrate) (PHB) and pita fibers derived from the agave plant (Agave americana). Various weight contents (10, 20, 30, and 40 wt.-%) of pita fibers at different lengths (5, 15, and 20 mm) were successfully incorporated into PHB by compression molding. The newly prepared PHB/pita fibers composite sheets were characterized in terms of their mechanical and thermomechanical properties and then related to their morphology after fracture. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 60 publications
(114 reference statements)
2
34
0
1
Order By: Relevance
“…This supports a recent finding in which it was indicated that particle debonding was the main failure mechanism of cellulosic fillers in biopolymer matrices (Torres-Giner et al, 2017). This occurs due to the lack of adhesion or cohesion at the particle-matrix interface of the green composite.…”
Section: Morphology Of Green Compositessupporting
confidence: 91%
See 1 more Smart Citation
“…This supports a recent finding in which it was indicated that particle debonding was the main failure mechanism of cellulosic fillers in biopolymer matrices (Torres-Giner et al, 2017). This occurs due to the lack of adhesion or cohesion at the particle-matrix interface of the green composite.…”
Section: Morphology Of Green Compositessupporting
confidence: 91%
“…The latter, i.e., the interfacial filler-matrix adhesion, is crucial since it is responsible for promoting a good stress transfer from the continuous phase to the dispersed fillers that must carry the load. Nevertheless, the high inherent hydrophilicity of cellulosic fillers does not habitually offer good adhesion with the hydrophobic or low hydrophilic polymers used as the composite matrix (Torres-Giner et al, 2017). Poor filler wetting causes a non-uniform distribution of fillers in the matrix, consequently aggregation and void formation is commonly observed during melt processing.…”
Section: Introductionmentioning
confidence: 99%
“…The strands were cooled in air, granulated in pellets in an air-knife unit, and dried at 60 • C for 72 h to remove moisture. Thereafter, the pellets were thermo-compressed using a 10-Tn hydraulic press from Robima S.A. (Valencia, Spain) equipped with two hot aluminum plates and a temperature controller from Dupra S.A. (Castalla, Spain) [53]. For this, about 5 g of each composition was thermo-compressed at 180 • C with a pressure of 40 MPa tons for 3 min in a square frame of 10 cm × 10 cm by two hot plates and air cooled at room conditions.…”
Section: Films Preparationmentioning
confidence: 99%
“…The latest research performed on green composites shows that the use of lignocellulosic materials obtained from industrial by‐products and food or agroforestry wastes is increasing as cost‐effective fillers since they provide a sustainability enhancement and improve physical performance . Some recent examples include, for instance, wood flour, banana fibers, rice husk, peanut skin, wheat and soy fibers, pita fibers and Posidonia oceanica seaweed . In the study reported in the present paper, for the first time, orange peel flour (OPF) was used as a lignocellulosic filler to develop green composites of PLA.…”
Section: Introductionmentioning
confidence: 96%